Identifying Effective Factors in Establishing Communication between Students and advisor Members of rehabilitation faculty of Hamadan University of Medical Sciences "Students' Point of View" - Saideh Sadat Mortazavi; Atta Heidari; Zahra Mortazavi; Maryam Seyedtabib (Zanjan University of Medical Sciences and Health Services, 2019)
Background & Objective: Effective teacher-student relationship plays a fundamental role in the effective increase of the counseling process. This study aimed to recognize the factors affecting the advisor-student relationship from the perspective of students in school of rehabilitation in Hamadan, Iran. Materials and Methods: This cross-sectional, descriptive study was performed on 117 students in the school of rehabilitation at Hamadan University of Medical Sciences. In this study, the teacher-student relationship questionnaire was applied in three individual, professional and scientific areas. Students filled the questionnaires through self-report, and data analysis was performed using descriptive statistics, independent t-test, and analysis of variance. Results: In this study, the mean scores related to three individual, professional, and scientific characteristics of advisors from the perspective of students were reported to be 4.07±0.4, 4.23±0.57, and 4.13±0.63, respectively. The items of sympathy with students, homogeneity of students and professors in terms of field of study, and having up-to-date knowledge in professors had the most impact on the teacher-student relationship, whereas the variables of age, gender and appearance had the least effect in this regard. Conclusion: According to the results of the study, the character and ethical aspect of professors can affect the improvement of the teacher-student relationship, thereby increasing and enhancing the counseling process.